Формирование знаний и представлений об окружающем мире в процессе познавательно-исследовательской деятельности детей старшего дошкольного возраста с задержкой психического развития посредством схем наглядного моделирования - Кухарева, М. В. (My University, 2016)
Currently, there is an increase in the number of children experiencing considerable difficulties in getting acquainted with the world. The article describes the conduct of pedagogical experiment with children mental retardation preschool age to build knowledge and ideas about the world in the process of cognitive research use of visual modeling schemes.
Keywords: impaired mental function; visual simulation; cognitive – research activity